Unravelling the mechanisms that determine the uptake and metabolism of magnetic single and multicore nanoparticles in a Xenopus laevis model. Issue 2 (15th December 2017) - Marín-Barba, M.; Gavilán, H.; Gutiérrez, L.; Lozano-Velasco, E.; Rodríguez-Ramiro, I.; Wheeler, G. N.; Morris, C. J.; Morales, M. P.; Ruiz, A.
Abstract : Nanoparticles' structure (single or multicore) and their surface chemistry determine how the embryos absorb and activate the iron metabolic pathway. Abstract : Multicore superparamagnetic nanoparticles have been proposed as ideal tools for some biomedical applications because of their high magnetic moment per particle, high specific surface area and long term colloidal stability. Through controlled aggregation and packing of magnetic cores it is possible to obtain not only single-core but also multicore and hollow spheres with internal voids. In this work, we compare toxicological properties of single and multicore nanoparticles. Both types of particles showed moderate in vitro toxicity (MTT assay) tested in Hep G2 (human hepatocellular carcinoma) and Caco-2 (human colorectal adenocarcinoma) cells. The influence of surface chemistry in their biological behavior was also studied after functionalization with O, O ′-bis(2-aminoethyl) PEG (2000 Da). For the first time, these nanoparticles were evaluated in a Xenopus laevis model studying their whole organism toxicity and their impact upon iron metabolism. The degree of activation of the metabolic pathway depends on the size and surface charge of the nanoparticles which determine their uptake. The results also highlight the potential of Xenopus laevis model bridging the gap between in vitro cell-based assays and rodent models for toxicity assessment to develop effective nanoparticles for biomedical applications.